Performance Analysis of Simplification of Hyperplane Support Vector Machine - Hui Cheng; Jinglong Fang; Daquan Wang; Xingqi Wang (Dianxin kexue)
Comparing with traditional support vector machine，hyperplane support vector machine （HPSVM）and hyperplane support vector machine for regression（HPSVMR）not only reduce the number of support vectors and calculation time but also have comparable accuracy.However，they have different simplification effect on different problems.The reasons for this phenomenon were analyzed，the conclusion that the lower the percentage of non-bound support vectors is，the more obvious the effect of simplification was pointed out.